1987
DOI: 10.1002/mds.870020301
|View full text |Cite
|
Sign up to set email alerts
|

Historical review: Abnormal movements associated with epidemic encephalitis lethargica

Abstract: Parkinsonism can result from numerous causes (1). Postinfectious etiologies are rare today but were common in the past. Postencephalitic parkinsonism was one of the most dramatic sequelae of encephalitis lethargica (von Economo's disease). This epidemic began in 1916-1917 in Austria, and cases had been reported throughout the world by 1919 (2). The two sexes were affected equally, and all races and occupations could be affected. The peak incidence in the United States was in 1923 with about 2,000 reported deat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0
2

Year Published

1989
1989
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 10 publications
1
13
0
2
Order By: Relevance
“…In the 1920's and 1930's, PEP was the commonest form of parkinsonism (Dimsdale, 1946) but steadily declined in incidence thereafter (Krusz et al, 1987). However, sporadic cases of PEP have been reported recently (Rail et al, 1981;Clough et al, 1983;Howard and Lees, 1987;Geddes et al, 1993;Barletta et al, 1995).…”
Section: Clinical Findingsmentioning
confidence: 94%
“…In the 1920's and 1930's, PEP was the commonest form of parkinsonism (Dimsdale, 1946) but steadily declined in incidence thereafter (Krusz et al, 1987). However, sporadic cases of PEP have been reported recently (Rail et al, 1981;Clough et al, 1983;Howard and Lees, 1987;Geddes et al, 1993;Barletta et al, 1995).…”
Section: Clinical Findingsmentioning
confidence: 94%
“…Environmental toxicants have been hypothesized to play a role based on the observations that parkinsonism can be caused by postencephalitic infection,3, 4 by accidental injection of MPTP 5 and by chronic manganese intoxication 6. Consistent with this view, human epidemiological studies have shown that rural living, exposure to herbicides, pesticides, and heavy metals increase the risk of PD 7-11.…”
mentioning
confidence: 99%
“…Postencephalitic parkinsonism was common in the period following the epidemic of encephalitic lethargica (13). Some cases called traumatic parkinsonism were probably postencephaltic in origin.…”
Section: James Parkinsonmentioning
confidence: 99%